1991
DOI: 10.1002/bip.360310211
|View full text |Cite
|
Sign up to set email alerts
|

A vibrational spectroscopic study of the self‐association of 5′‐GMP in aqueous solution

Abstract: The Raman spectra of highly concentrated solutions of 5'-GMP at neutral and acid pH were recorded in order to better characterize the structure of the self-aggregates formed in these solutions and their melting behavior. Vibrational coupling of the C=O stretching vibrations in tetrameric units at neutral pH is shown to yield a characteristic pattern of two Raman bands at ca. 1730 and 1680 cm-' (1708 and 1664 cm-' in D 2 0 ) , and an iractive mode at 1678 cm-' in D20. From the intensity of the 1730-cm-' band, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…27,37 In contrast, only one band at 1683 cm Ϫ1 was observed in the carbonyl region of the poly(rI) ir spectrum and this noncoincidence of Raman and ir bands is suggestive that a splitting of CAO bands occurs because of the C 4h symmetry of the tetrads and the interaction of adjacent tetrads within the complex. 27,37,38 More recent UVRR studies 28,39 observed only one C 6 AO mode for poly(rI) and G-tetrads, and the present study is consistent with these UVRR observations. It is possible that the FIGURE 9 UVRR spectra of poly(rI) measured with 210 nm excitation.…”
supporting
confidence: 95%
See 1 more Smart Citation
“…27,37 In contrast, only one band at 1683 cm Ϫ1 was observed in the carbonyl region of the poly(rI) ir spectrum and this noncoincidence of Raman and ir bands is suggestive that a splitting of CAO bands occurs because of the C 4h symmetry of the tetrads and the interaction of adjacent tetrads within the complex. 27,37,38 More recent UVRR studies 28,39 observed only one C 6 AO mode for poly(rI) and G-tetrads, and the present study is consistent with these UVRR observations. It is possible that the FIGURE 9 UVRR spectra of poly(rI) measured with 210 nm excitation.…”
supporting
confidence: 95%
“…38 The observed frequency downshift of the 1692 cm Ϫ1 mode upon H bonding and the cooperative nature of the frequency change with increasing temperature are consistent with the assignment of this mode to a localized CAO stretching vibration.…”
supporting
confidence: 72%
“…Many experimental and theoretical studies have revealed various dependencies of characteristic marker band frequencies on the effects of substituents and intermolecular interactions. 24 In particular, hydrogen-bonding-induced base pairing, 25,26 base stacking, 27,28 coordination of metal ions, [29][30][31] and more generally changes of surrounding electrostatic potential around a given NA subunit can be studied by analyzing magnitudes and signs of marker band frequency shifts. 24 In particular, hydrogen-bonding-induced base pairing, 25,26 base stacking, 27,28 coordination of metal ions, [29][30][31] and more generally changes of surrounding electrostatic potential around a given NA subunit can be studied by analyzing magnitudes and signs of marker band frequency shifts.…”
Section: Introductionmentioning
confidence: 99%
“…These bands have been related to the nC¼O stretch with contributions from hydrogen bonds or from interactions due to self-association processes of the guanine residues. [7][8][9][10][11] A medium band at 1643 cm À 1 in the IR spectrum stands out which is not observed in the spectra of the recrystallized samples. In this part of the spectrum, it is well known that bands from vibrations of water molecules are expected.…”
Section: Resultsmentioning
confidence: 69%
“…The mode that appears at $1480 cm À 1 being used in various studies as a marker of base stacking or metal ion bonding to the N7. [7] The frequency shift observed in the spectra may be explained in a similar way to the explanation given earlier for the 1567 cm À 1 band; namely changes of the overlapped components of the two bands at $1488 and 1477 cm À 1 . Between 1450 and 1300 cm À 1 there are important variations, both in the IR spectrum and the Raman spectrum (Fig.…”
Section: Resultsmentioning
confidence: 84%